Student Management in the Special Service Education Program - Utari, Toto Sutarto Gani; Kulkarni, Heramb; Firmansyah, Bambang; Fauzi, Ahmad (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to analyze the management process of special service education programs in PUI Cirebon City vocational high schools through planning, organizing, implementing, and supervising. This research uses qualitative methods with a case study approach. The data collection uses interview, observation, and documentation techniques. Data analysis uses data collection techniques, reduction, display, and conclusions. The results showed that the management pattern of students in special service education programs began with planning an analysis of prospective students by considering their capacity. Grouping students based on student origin and specialization. Coaching and student development are carried out by the teaching and learning process of visiting students for specialization subjects and visiting teachers for regional, national, and local subjects, emphasizing coaching and development in the vocational field. This research can have implications for education providers in addressing students' limited ability to learn through innovative programs such as special service education programs.